Carbon Monoxide and Particulate Matter Concentrations inside the Road Tunnels of Guanajuato City, Mexico - Adrián Zamorategui-Molina; Norma L. Gutiérrez-Ortega; Juan Carlos Baltazar-Vera; Julio Del Ángel-Soto; David Tirado-Torres (Aerosol and Air Quality Research)
Abstract In the city of Guanajuato, Mexico, road tunnels offer drivers an effective means of avoiding traffic congestion. Additionally, they enable pedestrians to reduce their travel time and distance. However, exposure to elevated levels of carbon monoxide (CO) and particulate matter (PM), including PM2.5 and PM10 consisting of vehicle-emitted particles and resuspended dust, poses risks to human health. Hence, we monitored the CO, PM2.5, and PM10 concentrations; wind speed; and number of vehicles in three popular tunnels among pedestrians, all of which exhibited relatively high levels of pollution, in Guanajuato. We evaluated the CO concentration using a portable non-dispersive infrared radiation (NDIR) sensor (ALTAIR Pro Single-Gas Detector) and the PM2.5 and PM10 concentrations using a handheld mass monitor equipped with a high-precision laser sensor (Aerocet 831). We then employed X-ray diffraction (XRD), X-ray fluorescence (XRF), and scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDS) to analyze the mineralogy, chemical composition, and morphology of the PM, respectively. Although the average CO concentration fell below the World Health Organization (WHO)’s guideline of 50 ppm for a 30-minute exposure, the average PM10 concentration exceeded the guideline of 50 µg m–3 for a 24-hour exposure inside all three tunnels. The high emission factors we found demonstrate the necessity of installing ventilation systems in these passageways. Lastly, the chemical components of the PM corresponded to the mineral dust originating from the eroded rock (mainly rhyolite), soil, and fortifying construction material inside the tunnels.